Economics of Tobacco Toolkit, Tool 7 : Understand, Measure, and Combat Tobacco Smuggling - Merriman, David (World Bank, Washington, DC, 2013)
The intended purpose of this tool is to let readers gain the necessary knowledge about tobacco smuggling. With this knowledge, policy responses can be developed and further monitored in order to establish their effectiveness, appropriateness, and impact on other policy goals. For example, if enhanced tax revenue is one goal of a tobacco taxation policy, smuggling can be an important consideration, since smuggled tobacco avoids taxation. Likewise, tobacco smuggling can have an impact on health policies, as it can be difficult to regulate health warnings and conditions of sale on smuggled tobacco. More specifically, by using the methods presented in this tool, a more accurate and objective understanding of tobacco smuggling can be gained. Tobacco manufacturers, distributors and sellers, and others with a narrow self-interest in the design of tobacco control policy often misrepresent the degree of tobacco smuggling. Well documented, methodologically sound, quantitative estimates of tobacco smuggling are a useful tool for educating policymakers about the costs and benefits of various policies. Moreover, unbiased estimates of smuggling, and the change in smuggling over time, are essential tools to evaluate the success of many tobacco control policies.